Identification of Priority Supply Areas for Carbon Sinks Based on Ecosystem Service Flow: A Case Study for the Hexi Region in Northwestern China - Meng Zhu; Yingqing Su; Qi Feng; Wei Liu; Yuanyuan Xue; Lingge Wang; Zexia Chen; Jutao Zhang (Land)
The development and implementation of regional protection plans for ecosystem carbon storage services have been recognized as crucial actions for mitigating global climate change. However, the supply areas of carbon sequestration in terms of ecosystem service flows in inland regions are still less evaluated. The goal of this study is to identify the priority-ranked supply areas for carbon sinks. Here, we conducted a case study in the Hexi Region of northwestern China and proposed a framework to quantify the priority supply areas for carbon sinks from the perspective of ecosystem service flows. Firstly, we quantified the carbon service supply and demand areas by combining carbon models (i.e., the Carnegie–Ames–Stanford Approach model and soil respiration models) with socioeconomic and natural factors. Then, we introduced a breaking point formula to estimate ecosystem service flow, specifically focusing on distance or range. Finally, we determined priority supply areas for carbon sinks based on the Zonation model. The results showed that significantly higher carbon sequestration values were detected in the Qilian Mountains, ranging from 2.0 to 3.0 t hm−2, in comparison with desert oasis areas, where the supply values ranged from 0 to 0.01 t hm−2. The urban areas and rural settlements within the study area are characterized by higher values of carbon emissions compared to those in the Qilian Mountains and deserts. The carbon flow analysis demonstrated that the middle and northern parts of the study area, being characterized by lower precipitation and sandy landscapes, were identified as locations with low carbon sequestration fluxes (<1.0 t hm−2). In addition, the mountainous regions were identified as the main highest priority area for ecosystem carbon sequestration, covering 8.33% of total area of the Hexi Region. Our findings highlighted the importance of the Qilian Mountains in terms of sustaining carbon sequestration service supply in the Hexi Region and targeted ecological protection practices to be implemented going forward.